SRI LANKA OXYGEN READINESS AND STRATEGIES ADAPTED FOR COVID-19 PATIENTS’ MANAGEMENT - Liyanage, Dilip Hukkaduwa; Krishanth, Maddage Don Athula; Wickramaratne, Peththahandi Nadhee; Alwis, Adimalee Kankanamalage Sunil Bernard De; Pannapitiya, Pannapitiyage Wijeyala Chandrasiri; Perera, Udawatta Arachchige Anura Sampath; Yaddehige, Iranga Sachinthika (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2022)
Background: Shortly after the Covid-19 oxygen crisis in India, the Sri Lanka Ministry of Health started investigating and analyzing gaps in oxygen production, supplies and demands. Aims: This study aimed to evaluate the preparedness in Covid-19 cases management and recommend strategies to prevent oxygen crisis in healthcare facilities. Methods: This study used information on oxygen source redundancy and delivery methods to assess whether a healthcare facility is prepared to provide the necessary oxygen demand for patients in need and to estimate the number of patients that can be treated with the currently available oxygen supplies. The predicted oxygen supplies and demands were assessed with a panel of experts using qualitative and quantitative methods. Data were collected using the Health Information Update System. Results: Sri Lanka had 39,529 designated hospital beds including Intensive Care Unit and High Dependency Unit beds for Covid-19 patients. Even though an average number of patients were reaching 30,000, the actual oxygen demands were around 1,200 which were easily manageable with the current capacity of 80 tons per day. Conclusions: Sri Lanka has made progress to increase access to oxygen by using novel methods to procure and increase oxygen availability, storing, and carrying capacity.